Modelling the national economic burden of non-surgical periodontal management in specialist clinics in Malaysia using a markov model - Ainol Haniza Kherul Anuwar; Chiu Wan Ng; Syarida Hasnur Safii; Roslan Saub; Norintan Ab-Murat (BMC, 2024)
Abstract Background Non-surgical periodontal treatment is the mainstay of periodontal treatment. In Malaysia, the prevalence of periodontal disease is substantial among adults with almost half of them having periodontitis. Therefore, we estimated the economic burden of non-surgical periodontal treatment in specialist clinics in Malaysia. Methods Relevant data from multiple data sources which include national oral health and health surveys, national census, extensive systematic literature reviews, as well as discussion with experts, were used to estimate the economic burden of non-surgical periodontal management in specialist clinics in Malaysia in 2020. This estimation was done from the oral healthcare provider's perspective in both public and private sectors using an irreducible Markov model of 3-month cycle length over a time horizon of one year. Results In 2020, the national economic burden of non-surgical periodontal treatment during the first year of periodontal management in specialist clinics in Malaysia was MYR 696 million (USD 166 million), ranging from MYR 471 million (USD 112 million) to MYR 922 million (USD 220 million). Of these, a total of MYR 485 million (USD 115 million) and MYR 211 million (USD 50 million) were the direct oral healthcare cost in public and private dental clinics, respectively. Conclusion The findings of this study demonstrated substantial economic burden of non-surgical periodontal management in specialist clinics in Malaysia. Being a life-long disease, these findings highlight the importance of enforcing primary and secondary preventive measures. On the strength and reliability of this economic evidence, this study provides vital information to inform policy- and decision-making regarding the future direction of managing periodontitis in Malaysia.